Highest Efficiency Dssc Fabrication With Natural Dye and Chemical Dye - Assegaf, Sufiyah (International Journal of Education, Information Technology, and Others, 2024)
DSSC fabrication can be carried out using various methods, such as hydrothermal, doctor blade technique, sol gel spin coating method. With electrolytes such as I2/I3-, KI, ZnO, TiO2 in DSSC fabrication. The greatest efficiency for natural dyes is around 2.68%, while for chemical dyes it is 10.4%. Efficiency is influenced by the concentration of the dye and the type of electrolyte used. From several DSSC manufacturing methods described previously, with natural and chemical dyes, it can be concluded that what influences the high efficiency of DSSC is as follows. Dyes, these dyes must have high light absorption values in the long range. broad waves, as well as the ability to produce stable electrons after absorbing light photons. The liquid electrolyte in DSSC plays a role in conducting electrons between the dye and the electrode. The type and quality of electrolyte can affect the electron transfer rate and energy conversion efficiency. Electrodes, electrodes are components in DSSC which function to collect electrons produced by the dye and channel them to the solar cell. Electrode material and good contact between the electrode and the sensitizer material also have an impact on DSSC efficiency. Solar cell design, DSSC solar cell design including layer structure and electrode configuration can affect energy conversion efficiency. Good design can maximize light absorption and reduce energy loss. Light Intensity: The efficiency of a DSSC depends on the intensity of sunlight it receives. High DSSC efficiency when direct or high sunlight. Temperature during DSSC operation, high temperatures can increase electron mobility and speed up chemical reactions in solar cells, but must be managed properly so as not to damage DSSC components. Damage to DSSC components can reduce DSSC efficiency. To make DSSc with natural dyes, the method used by Helga et al produces an efficiency of 2.68% compared to the method used by Utami et al which only produces 0.72%. To make DSSC with chemical dyes, the method used by Whon Chu et al, Suruthi Priya Nagalingam, Anurag Roy et al, and M. Chinnari produces the greatest efficiency of 10.4%. This efficiency is produced by research by Whun Chun Oh et al. So it can be concluded that to produce higher efficiency, method optimization needs to be carried out in the research of Helga et al and Whun Chun Oh.